Crystalline silicon-perovskite laminated solar cell and preparation method thereof
By forming a composite optical structure on the surface of crystalline silicon, the wettability of perovskite precursor body fluids is improved, and the problem of poor coverage of perovskite on the pyramid structure is solved, reflection loss is reduced, and the efficiency of perovskite/silicon stacked solar cells is improved.
Patent Information
- Application Number
- CN202411580238.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-04-01
AI Technical Summary
It is difficult for existing perovskite/silicon stacked solar cells to achieve good coverage of solution perovskites on the pyramid structure, resulting in large reflection losses and affecting battery efficiency.
By improving the wettability of perovskite precursor body fluids and antisolvents, combining the composite optical structure of micro-optical structure and nano-optical structure, the reflection loss between perovskite and crystalline silicon and air interface is reduced, and good coverage of perovskites is achieved.
It effectively reduces the reflection loss between perovskite and crystalline silicon and air interface, improves the photoelectric coupling and optical correspondence of perovskite top cells, and improves the efficiency of the overall solar cell.
Smart Images

Figure CN119744069A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of tandem solar cells, and in particular to a crystalline silicon-perovskite tandem solar cell and a preparation method thereof. Background Art
[0002] The development of crystalline silicon solar cells has reached a bottleneck, and its highest efficiency has reached 27.1%, which is very close to the theoretical limit of 29.4% for crystalline silicon solar cells. However, perovskite / silicon tandem solar cells, with a theoretical limit efficiency of up to 46%, are considered to be the next generation of new photovoltaic technology that is most likely to break through the theoretical limit of single junction.
[0003] At present, perovskite / silicon tandem solar cells generally use silicon-bottom cells based on planar structures or silicon-bottom cells based on pyramid structures. Silicon-bottom cells with planar structures have serious reflection losses at the interface between perovskite and silicon, and it is difficult to achieve good coverage of solution-processed perovskites with traditional pyramid structures. Although solution-processed coverage on pyramid structures can be achieved by reducing the size of the pyramids and increasing the thickness of the perovskites, reducing the size of the pyramids will affect the optical performance of the cells, and increasing the thickness of the perovskites will cause the performance of the cells to decrease due to insufficient carrier diffusion length. Therefore, how to conformally deposit perovskites on pyramid structures by solution methods to simultaneously reduce the reflection losses at the air / perovskite and perovskite / crystalline silicon interfaces and achieve good coverage of solution-processed perovskites is of great significance for further improving the efficiency of perovskite / silicon tandem cells, and is an urgent problem to be solved in the field of perovskite / silicon tandem solar cells. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a crystalline silicon-perovskite tandem solar cell and a preparation method thereof, which improves the wettability of the perovskite precursor liquid and the anti-solvent, can achieve good coverage of the solution-processed perovskite, and can also effectively reduce the reflection loss at the two interfaces of the perovskite and the crystalline silicon and the perovskite and the air, which is beneficial to improving the efficiency of the crystalline silicon-perovskite tandem solar cell.
[0005] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a crystalline silicon-perovskite tandem solar cell, comprising a crystalline silicon bottom cell and a perovskite top cell, wherein the crystalline silicon in the crystalline silicon bottom cell has a composite optical structure, wherein the composite optical structure comprises a micron-optical structure and a nano-optical structure, wherein the micron-optical structure is formed in situ on the surface of the crystalline silicon, wherein the nano-optical structure is formed in situ on the micron-optical structure, wherein the micron-optical structure has a micron structure distributed in a periodic array or randomly distributed, and wherein the nano-optical structure has a nanostructure distributed in a periodic array or randomly distributed.
[0006] In the crystalline silicon-perovskite tandem solar cell provided by the present invention, the crystalline silicon has a composite optical structure composed of a micron optical structure and a nano-optical structure, and the components of the nano-optical structure and the micron optical structure in the composite optical structure are all silicon. First, in terms of forming a perovskite film, the nano-optical structure can be used as a nano-support for the nucleation and growth of perovskite grains, which can not only improve the wettability of the perovskite precursor liquid and the anti-solvent by reducing the surface energy of the crystalline silicon, but also induce the vertical growth of the perovskite from bottom to top through the nano-confinement effect, so as to form a high-quality perovskite film with good coverage on the surface of the crystalline silicon, and at the same time improve the extraction and collection of carriers in the perovskite top cell. Secondly, in terms of optics, on the one hand, the nano-optical structure can also provide an effective gradient refractive index to reduce the reflection loss at the interface between the perovskite and the crystalline silicon, and improve the photoelectric coupling effect of the perovskite top cell; on the other hand, the micron optical structure can reduce the reflection loss at the interface between the perovskite and the air, and increase the optical path of the incident light, thereby improving the optical response of the perovskite top cell in the tandem cell. In terms of material properties, the composite optical structure provided by the present invention is directly formed on the surface of crystalline silicon, has a more firm bond with the substrate, has better thermal stability in high-temperature environments, has higher mechanical strength and durability, and is not easily fallen off or affected by environmental factors; the composite optical structure also has a higher light capture efficiency, especially in reducing surface reflections, can trap light more effectively, increase the path length of light in the material, and improve the photoelectric conversion efficiency.
[0007] In a possible implementation manner, the crystalline silicon bottom cell is a silicon homojunction and a silicon heterojunction.
[0008] Furthermore, the crystalline silicon bottom cell has any one of the cell structures of a tunneling oxygen passivation contact silicon bottom cell, a heterojunction silicon bottom cell, a full back electrode contact silicon bottom cell and a passivation emitter back field contact silicon bottom cell.
[0009] In one possible implementation, the perovskite top cell is a perovskite solar cell based on a PIN or NIP structure.
[0010] In a possible implementation, the microstructure includes one or more of microholes, microcolumns, microcones, microtubes, microspheres, microhemispheres, micropyramids, microinverted pyramids, and microbars.
[0011] In one possible implementation, the nanostructure includes one or more of a nanohole, a nanowire, a nanocolumn, a nanocone, a nanotube, a nanosphere, a nanohemisphere, a nanopyramid, a nanoinverted pyramid, and a nanostrip.
[0012] In a possible implementation manner, the size of the microstructure is 1-50 μm, preferably 5-20 μm.
[0013] In a possible implementation, the size of the nanostructure is 0.1-500 nm, preferably 10-300 nm.
[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned crystalline silicon-perovskite tandem solar cell, comprising the following steps: S1. performing micron etching on the surface of a crystalline silicon substrate to form a micron optical structure with a periodic array distribution or a random distribution; S2, performing nano-etching on the surface of the micron optical structure in step S1 to form a nano-optical structure with periodic array distribution or random distribution, and obtaining a composite optical structure crystalline silicon; S3, depositing a passivation layer on both sides of the composite optical structure crystalline silicon in step S2, and then depositing an n-type transmission layer or a p-type transmission layer on the passivation layers on both sides of the composite optical structure crystalline silicon, respectively, and then depositing an intermediate composite layer on the front side of the composite optical structure crystalline silicon to obtain a crystalline silicon bottom cell preform; S4. On the front side of the crystalline silicon bottom cell preform described in step S3, a perovskite transmission layer, a perovskite active layer, a perovskite transmission layer, a front electrode buffer layer, a front electrode, a back electrode and a front anti-reflection layer are sequentially deposited to obtain a crystalline silicon-perovskite laminated solar cell.
[0015] The method for preparing a crystalline silicon-perovskite tandem solar cell provided by the present invention directly forms a composite optical structure including a micron optical structure and a nano optical structure on the surface of crystalline silicon by etching. Compared with nano structures and micro structures formed by other methods (such as spraying), the method for preparing a crystalline silicon-perovskite tandem solar cell provided by the present invention has the following advantages: (1) Precise control of the morphology of the composite optical structure: the morphology and size of the micro-nano structure can be precisely controlled by adjusting the etching process parameters (such as etching time, etching depth and chemical reaction rate), providing more consistent surface characteristics and better optical design freedom; (2) Reducing interface defects: Nanostructures or microstructures formed by other methods (such as spraying) are prone to introducing additional interfaces between the micro-nanostructure and the substrate, which may lead to interface defects or interface unevenness. The etching process is directly processed on the substrate, reducing interface defects, thereby improving the optoelectronic performance of the device; (3) Less surface contamination: The etching process for preparing the composite optical structure of the present invention is usually carried out under clean conditions, directly forming the structure, reducing the possibility of introducing impurities or contamination, and improving the surface cleanliness and performance of the device; (4) Better production repeatability and consistency: The etching process for preparing the composite optical structure of the present invention can achieve high repeatability production through standardized equipment and processes, while other methods (such as spraying) are affected by factors such as coating thickness and uniformity, and have relatively poor repeatability and consistency.
[0016] In a possible implementation, the micro-etching and the nano-etching are performed by wet etching and / or dry etching, the wet etching includes one or more of immersion etching, spray etching and photolithography, and the dry etching includes one or more of physical etching, chemical etching and physicochemical etching.
[0017] Furthermore, the wet etching is solution etching.
[0018] Further preferably, the solution components of the solution etching include one or more of potassium hydroxide, sodium hydroxide and tetramethylammonium hydroxide.
[0019] More preferably, the solution composition also includes additives.
[0020] Furthermore, the dry etching is reactive ion etching or nanoimprint etching.
[0021] Further preferably, the process of reactive ion etching is to prepare a micron / nanometer mask layer on the surface of the crystalline silicon and then perform reactive ion etching.
[0022] Further preferably, the reaction gas of the reactive ion etching is any mixed gas of Cl2 and SF6, Cl2, SF6 and O2, Cl2, SF6, CF4 and O2, or Cl2, BCl3 and Ar.
[0023] Further preferably, the reactive ion etching chamber has a gas pressure of 15-25 Pa.
[0024] Further preferably, the process of the nanoimprint etching is to prepare a pattern template for nanoimprint etching, imprint the pattern template on the surface of the crystalline silicon by nanoimprinting, and then perform etching.
[0025] In a possible implementation, the deposition method of the perovskite transport layer is solution deposition.
[0026] Furthermore, the solution deposition includes any one of spin coating, blade coating and slit coating.
[0027] In a possible implementation, the nano-etching method further includes a pore expansion process, wherein the pore expansion process is as follows: firstly, the nano-optical structure is placed in a solution containing an acid, an alkali or a hydrogen peroxide solution for pore expansion, then the surface oxide layer is removed with hydrofluoric acid, and then the surface metal ions are removed with nitric acid. Through the pore expansion process, the photoelectric conversion efficiency of the crystalline silicon-perovskite laminated solar cell can be further improved.
[0028] The above-mentioned implementation modes can be combined arbitrarily based on the common sense in the art.
[0029] The reagents and raw materials used in the present invention are commercially available.
[0030] The positive and progressive effects of the present invention are: In the crystalline silicon-perovskite tandem solar cell provided by the present invention, the crystalline silicon has a composite optical structure composed of a micron optical structure and a nano-optical structure. The micron optical structure and the nano-optical foot bone can serve as a nano-support for the nucleation and growth of perovskite grains, which can not only improve the wettability of the perovskite precursor solution and the anti-solvent by reducing the polar component of the surface energy of the crystalline silicon, but also facilitate the retention of the solvent on the surface during the growth process; at the same time, the micron optical structure can also reduce the reflection loss at the interface between the perovskite and the air, and increase the optical path of the incident light, thereby reducing the reflection loss of the top cell; the nano-optical structure can reduce the reflection loss by gradually changing the refractive index at the interface, and improve the band edge of the top cell by coupling the short-wave incident light. The light absorption of the bottom cell in the near-infrared band can be improved by improving the scattering and optical path of the incident light; the high dispersion component of the nano-optical structure can improve the wettability of the perovskite and the anti-solvent, which is beneficial to the large-area preparation of well-coated perovskite; the low polarity component of the nano-optical structure is beneficial to improving the barrier capacity of the interface to water and oxygen, and preventing the intrusion of water vapor in the air; the nano-optical structure can promote the longitudinal growth of perovskite grains through the nano-confinement effect, improve the crystal quality, reduce the number of grain boundaries and surface defects, and promote carrier transport; the nano-optical structure helps to release the residual stress formed during the annealing process inside the perovskite film, prevent the accumulation of stress, increase the activation energy of ion migration, and improve the long-term stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a cross-sectional SEM morphology of the perovskite prepared on the composite optical structure crystalline silicon in Example 1.
[0032] Figure 2 This is a current-voltage curve of the crystalline silicon-perovskite tandem solar cell prepared in Example 1.
[0033] Figure 3 This is a SEM morphology image of the composite optical structure crystalline silicon prepared in Example 4.
[0034] Figure 4 This is a cross-sectional SEM morphology image of the perovskite prepared on the composite optical structure crystalline silicon in Example 4.
[0035] Figure 5 This is a current-voltage curve of the crystalline silicon-perovskite tandem solar cell prepared in Example 4. DETAILED DESCRIPTION
[0036] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0037] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0038] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.
[0039] Example 1 The present embodiment provides a crystalline silicon-perovskite tandem solar cell, comprising a crystalline silicon bottom cell and a perovskite top cell, wherein the crystalline silicon in the crystalline silicon bottom cell has a composite optical structure consisting of a micron optical structure and a nano-optical structure, the micron optical structure is formed in situ on the surface of the crystalline silicon, the nano-optical structure is formed in situ on the surface of the micron optical structure, the micron optical structure is used to reduce the reflection loss at the interface between the perovskite and the air, the nano-optical structure serves as a nano support for the nucleation and growth of perovskite grains and is used to reduce the reflection loss at the interface between the perovskite and the crystalline silicon; the micron optical structure is a randomly distributed micron pyramid structure, the size of the micron pyramid is 3-7 μm, the nano-optical structure has a randomly distributed nanowire structure, and the diameter of the nanowire is about 50 nm.
[0040] It is prepared by the following steps: (1) The n-type polished crystalline silicon cleaned by the RCA standard cleaning method was placed in a mixed solution of sodium hydroxide and isopropanol, where the concentration of sodium hydroxide was 25 g / L and the concentration of isopropanol was 12.5 g / L, and etched at 80 °C for 10 min to perform double-sided micron pyramid etching to obtain a micron optical structure with randomly distributed pyramid structures; (2) placing the micron optical structure in step (1) in a pretreatment solution for nano-etching treatment, wherein the pretreatment solution is a mixture of hydrofluoric acid, hydrogen peroxide, silver nitrate and isopropyl alcohol, wherein the concentration of silver nitrate is 96 µmol / L, the mass concentration of hydrofluoric acid is 40%, and the mass concentration of hydrogen peroxide is 30%. The nano-etching treatment temperature is 25°C and the time is 3 min, followed by rinsing with deionized water for 2 min, thereby obtaining a nanowire structure on the surface of the micron pyramid and obtaining a composite optical structure crystalline silicon; (3) Soaking the composite optical structure crystalline silicon obtained in step (2) in concentrated nitric acid with a mass concentration of 68% for 3 minutes and then rinsing with deionized water for 2 minutes. Then, using PECVD deposition technology and nitrous oxide as a reaction gas, a silicon oxide passivation layer is deposited on both sides of the crystalline silicon. Then, using PECVD deposition technology, phosphorus- and boron-doped amorphous silicon thin film precursors are deposited on the silicon oxide layers on both sides of the crystalline silicon, respectively. Annealing is performed in a tube furnace at a temperature of 900 °C for 50 minutes to crystallize the thin film and activate the doped atoms to form n- and p-type polycrystalline silicon transport layers, thereby obtaining a crystalline silicon bottom cell. (4) First, remove the oxide layer of the crystalline silicon bottom cell in step (3) by HF, and deposit aluminum oxide on the front and back surfaces of the crystalline silicon bottom cell by an atomic layer deposition system, followed by annealing and hydrogen injection; deposit a buffer layer by thermal evaporation; and then deposit a TCO composite layer by PVD deposition technology; deposit a nickel hexahydrate and nitrate film on the side of the crystalline silicon bottom cell having an n-type polycrystalline silicon transport layer by spin coating technology, and anneal at 360°C to form a nickel oxide film hole transport layer; deposit a perovskite film on the surface of the nickel oxide film by spin coating technology; deposit C60 and bathocuproine (BCP) electron transport layers on the surface of the perovskite film by thermal evaporation; deposit an IZO transparent electrode on the BCP surface by magnetron sputtering deposition technology; and deposit a metal frame electrode on the surface and back of the IZO by magnetron sputtering deposition technology to obtain a crystalline silicon-perovskite stacked solar cell.
[0041] Figure 1 This is a cross-sectional SEM morphology of the perovskite prepared on the composite optical structure crystalline silicon in Example 1. The dark part in the figure is the crystalline silicon bottom cell, and the light part is the perovskite. It can be seen from the figure that the perovskite is evenly covered on the composite optical structure crystalline silicon.
[0042] Figure 2 : is a current-voltage curve of the crystalline silicon-perovskite tandem solar cell prepared in this embodiment. It can be seen from the figure that the current density J of the crystalline silicon-perovskite tandem solar cell prepared in this embodiment is sc 19.7 mA / cm 2 , voltage V OC is 1.74 V.
[0043] Table 1 shows the performance data of the crystalline silicon-perovskite tandem solar cell prepared in this embodiment. As can be seen from the table, the PCE efficiency of the crystalline silicon-perovskite tandem solar cell prepared in this embodiment has reached 25.1%.
[0044] Table 1 Performance data of crystalline silicon-perovskite tandem solar cells prepared in Example 1 Voc(V) FF(%) <![CDATA[J SC (mA / cm 2 )]]> PCE(%) Front Sweep 1.74 73.2 19.7 25.1 Backsweep 1.75 75.8 19.7 26.1
[0045] Example 2
[0046] The present embodiment provides a crystalline silicon-perovskite tandem solar cell, comprising a crystalline silicon bottom cell and a perovskite top cell, wherein the crystalline silicon in the crystalline silicon bottom cell has a composite optical structure consisting of a micron optical structure and a nano-optical structure, the micron optical structure is formed in situ on the surface of the crystalline silicon, the nano-optical structure is formed in situ on the micron optical structure, the micron optical structure is used to reduce the reflection loss at the interface between the perovskite and the air, the nano-optical structure serves as a nano support for the nucleation and growth of perovskite grains and is used to reduce the reflection loss at the interface between the perovskite and the crystalline silicon; the micron optical structure has a randomly distributed micron pyramid structure, the size of the micron pyramid is 5-12 μm, the nano-optical structure has a randomly distributed nanowire structure, and the diameter of the nanowire is about 70 nm.
[0047] It is prepared by the following steps: (1) The n-type polished crystalline silicon cleaned by the RCA standard cleaning method was placed in a mixed solution of sodium hydroxide and isopropanol, where the concentration of sodium hydroxide was 30 g / L and the concentration of isopropanol was 10 g / L, and etched at 80 °C for 10 min to perform double-sided micron pyramid etching to obtain a micron optical structure with a randomly distributed pyramid structure; (2) placing the micron optical structure in step (1) in a pretreatment solution for nano-etching treatment, wherein the pretreatment solution is a mixture of hydrofluoric acid, hydrogen peroxide, silver nitrate and isopropyl alcohol, wherein the concentration of silver nitrate is 98 µmol / L, the mass concentration of hydrofluoric acid is 45%, and the mass concentration of hydrogen peroxide is 30%. The nano-etching treatment temperature is 25°C and the time is 3 min. Subsequently, the nano-etching treatment is rinsed with deionized water for 2 min to obtain a nanowire structure on the surface of the micron pyramid, thereby obtaining a composite optical structure crystalline silicon; (3) Soaking the crystalline silicon obtained in step (2) in concentrated nitric acid with a mass concentration of 78% for 3 minutes and then rinsing with deionized water for 2 minutes. Then, using PECVD deposition technology and nitrous oxide as a reaction gas, a silicon oxide passivation layer is deposited on both sides of the crystalline silicon. Then, using PECVD deposition technology, phosphorus- and boron-doped amorphous silicon thin film precursors are deposited on the silicon oxide layers on both sides of the crystalline silicon, respectively. Annealing is performed in a tube furnace at a temperature of 800 °C for 90 minutes to crystallize the thin film and activate the doped atoms to form n- and p-type polysilicon transport layers, thereby obtaining a crystalline silicon bottom cell. (4) First, remove the oxide layer of the crystalline silicon bottom cell preform in step (3) by HF, deposit aluminum oxide on the front and back surfaces of the crystalline silicon bottom cell by an atomic layer deposition system, and then anneal and inject hydrogen; deposit a buffer layer by thermal evaporation; then deposit a TCO composite layer by PVD deposition technology; deposit a nickel hexahydrate and nitrate film on the side of the crystalline silicon bottom cell with an n-type polycrystalline silicon transport layer by spin coating technology, and anneal at 300°C to form a nickel oxide film hole transport layer; deposit a perovskite film on the surface of the nickel oxide film by spin coating technology; deposit C60 and bathocuproine (BCP) electron transport layers on the surface of the perovskite film by thermal evaporation; deposit an IZO transparent electrode on the BCP surface by magnetron sputtering deposition technology; and deposit a metal frame electrode on the surface and back of the IZO by magnetron sputtering deposition technology to obtain a crystalline silicon-perovskite stacked solar cell.
[0048] Example 3
[0049] The present embodiment provides a crystalline silicon-perovskite tandem solar cell, comprising a crystalline silicon bottom cell and a perovskite top cell, wherein the crystalline silicon in the crystalline silicon bottom cell has a composite optical structure consisting of a micron optical structure and a nano-optical structure, the micron optical structure is formed in situ on the surface of the crystalline silicon, the nano-optical structure is formed in situ on the micron optical structure, the micron optical structure is used to reduce the reflection loss at the interface between the perovskite and the air, the nano-optical structure serves as a nano support for the nucleation and growth of perovskite grains and is used to reduce the reflection loss at the interface between the perovskite and the crystalline silicon; the micron optical structure is a randomly distributed micron pyramid structure, the size of the micron pyramid is 8-20 μm, the nano-optical structure has a randomly distributed nanowire structure, and the diameter of the nanowire is about 120 nm.
[0050] It is prepared by the following steps: (1) The n-type polished crystalline silicon cleaned by the RCA standard cleaning method was placed in a mixed solution of sodium hydroxide and isopropanol, where the concentration of sodium hydroxide was 35 g / L and the concentration of isopropanol was 12.5 g / L, and etched at 100 °C for 10 min to perform double-sided micron pyramid etching to obtain a micron optical structure with a randomly distributed pyramid structure; (2) placing the micron optical structure in step (1) in a pretreatment solution for nano-etching treatment, wherein the pretreatment solution is a mixture of hydrofluoric acid, hydrogen peroxide, silver nitrate and isopropanol, wherein the concentration of silver nitrate is 100 µmol / L, the mass concentration of hydrofluoric acid is 50%, and the mass concentration of hydrogen peroxide is 35%. The nano-etching treatment temperature is 25°C and the time is 3 min. Subsequently, the nano-etching treatment is rinsed with deionized water for 2 min, and a randomly distributed nanowire structure is obtained on the surface of the micron pyramid, thereby obtaining a composite bag optical structure crystalline silicon; (3) soaking the composite optical structure crystalline silicon obtained in step (2) in concentrated nitric acid with a mass concentration of 68% for 3 minutes and then rinsing with deionized water for 2 minutes, then using PECVD deposition technology and nitrous oxide as a reaction gas to deposit a silicon oxide passivation layer on both sides of the composite optical structure crystalline silicon, and then using PECVD deposition technology to deposit phosphorus and boron doped amorphous silicon thin film precursors on the silicon oxide layers on both sides of the composite optical structure crystalline silicon, and annealing at a temperature of 1000 ° C for 10 in a tube furnace to crystallize the thin film and activate the doped atoms to form n- and p-type polycrystalline silicon transmission layers, thereby obtaining a crystalline silicon bottom cell; (4) First, remove the oxide layer of the crystalline silicon bottom cell in step (3) by HF, and deposit aluminum oxide on the front and back surfaces of the crystalline silicon bottom cell by an atomic layer deposition system, followed by annealing and hydrogen injection; deposit a buffer layer by thermal evaporation; and then deposit a TCO composite layer by PVD deposition technology; deposit a nickel hexahydrate and nitrate film on the side of the crystalline silicon bottom cell having an n-type polycrystalline silicon transport layer by spin coating technology, and anneal at 360°C to form a nickel oxide film hole transport layer; deposit a perovskite film on the surface of the nickel oxide film by spin coating technology; deposit C60 and bathocuproine (BCP) electron transport layers on the surface of the perovskite film by thermal evaporation; deposit an IZO transparent electrode on the BCP surface by magnetron sputtering deposition technology; and deposit a metal frame electrode on the surface and back of the IZO by magnetron sputtering deposition technology to obtain a crystalline silicon-perovskite stacked solar cell.
[0051] Example 4 The present embodiment provides a crystalline silicon-perovskite tandem solar cell, comprising a crystalline silicon bottom cell and a perovskite top cell, wherein the crystalline silicon in the crystalline silicon bottom cell has a composite optical structure consisting of a micron-optical structure and a nano-optical structure, the micron-optical structure is formed in situ on the surface of the crystalline silicon, the nano-optical structure is formed in situ on the micron-optical structure, the micron-optical structure is used to reduce the reflection loss at the interface between the perovskite and the air, the nano-optical structure serves as a nano-support for the nucleation and growth of perovskite grains and is used to reduce the reflection loss at the interface between the perovskite and the crystalline silicon; the micron-optical structure is a randomly distributed micron-pyramid structure, the size of the micron-pyramid is 3-7 μm, and the nano-optical structure has a randomly distributed nano-bowl structure.
[0052] It is prepared by the following steps: (1) The n-type polished crystalline silicon cleaned by the RCA standard cleaning method was placed in a mixed solution of sodium hydroxide and isopropanol, where the concentration of sodium hydroxide was 25 g / L and the concentration of isopropanol was 12.5 g / L, and etched at 80 °C for 10 min to perform double-sided micron pyramid etching to obtain a micron optical structure with a randomly distributed pyramid structure; (2) placing the micron optical structure in step (1) in a pretreatment solution for nano-etching treatment, wherein the pretreatment solution is a mixture of hydrofluoric acid, hydrogen peroxide, silver nitrate and isopropyl alcohol, wherein the concentration of silver nitrate is 96 µmol / L, the mass concentration of hydrofluoric acid is 40%, and the mass concentration of hydrogen peroxide is 30%. The nano-etching treatment temperature is 25°C and the time is 3 min, followed by rinsing with deionized water for 2 min, to obtain a nanowire structure on the surface of the micron pyramid; (3) soaking the nanowire structure obtained in step (2) in concentrated nitric acid with a mass concentration of 68% for 3 minutes, then rinsing with deionized water for 2 minutes, and then using a 5% sodium hydroxide aqueous solution to expand the nanowires for 20 seconds, and then using a mixed solution of hydrofluoric acid, hydrochloric acid and water in a mass ratio of 3:5:12 to remove metal ions on the surface of the crystalline silicon, forming a nano-optical structure with a nano-bowl structure, and obtaining a composite optical structure crystalline silicon; (4) The two sides of the composite optical structure crystalline silicon were treated with concentrated nitric acid to generate a silicon oxide passivation layer. Then, the PECVD deposition technology was used to deposit phosphorus- and boron-doped amorphous silicon thin film precursors on the silicon oxide layers on both sides of the crystalline silicon. The thin film was annealed at 900 °C for 50 min in a tube furnace to crystallize the film and activate the doped atoms to form n- and p-type polycrystalline silicon transport layers, thereby obtaining a crystalline silicon bottom cell. (5) First, remove the oxide layer of the crystalline silicon bottom cell in step (3) by HF, deposit aluminum oxide on the front and back surfaces of the crystalline silicon bottom cell by an atomic layer deposition system, and then anneal and inject hydrogen; deposit a buffer layer by thermal evaporation; then deposit a TCO composite layer by PVD deposition technology; deposit a MeO-2PACz hole transport layer on the side of the crystalline silicon bottom cell with an n-type polycrystalline silicon transport layer by spin coating technology; deposit a perovskite film on the surface of the MeO-2PACz hole transport layer by spin coating technology; deposit C60 and bathocuproine (BCP) electron transport layers on the surface of the perovskite film by thermal evaporation; deposit an IZO transparent electrode on the BCP surface by magnetron sputtering deposition technology; and deposit a metal frame electrode on the surface and back of the IZO by magnetron sputtering deposition technology to obtain a crystalline silicon-perovskite stacked solar cell.
[0053] Figure 3This is a SEM morphology image of the composite optical structure crystalline silicon prepared in this embodiment. It can be seen from the image that the surface of the crystalline silicon has a micron-optical structure composed of randomly distributed micron structures in the shape of pyramids, and the micron-optical structure also has a nano-optical structure in the form of a nano-bowl structure.
[0054] Figure 4 is a cross-sectional SEM morphology of the perovskite prepared on the composite optical structure crystalline silicon in Example 4, Figure 4 Figure (a) is a cross-sectional view at low magnification. It can be seen from the figure that the perovskite covers a large area evenly on the surface of the composite optical structure crystalline silicon. Figure 4 Figure (b) is a cross-sectional view at a high magnification. It can be seen from the figure that the thickness of the titanotite covering the surface of the crystalline silicon is also relatively consistent.
[0055] Figure 5 : is the current-voltage curve of the crystalline silicon-perovskite tandem solar cell prepared in Example 4. As can be seen from the figure, the current density Jsc of the crystalline silicon-perovskite tandem solar cell prepared in this example is 20.0 mA / cm 2 , the voltage VOC is 1.8 V.
[0056] Table 2 shows the performance data of the crystalline silicon-perovskite tandem solar cell prepared in Example 4. It can be seen from the table that the PCE efficiency of the crystalline silicon-perovskite tandem solar cell prepared in this example has reached 30.7%.
[0057] Table 2 Performance data of crystalline silicon-perovskite tandem solar cells prepared in Example 4 Voc(V) FF(%) <![CDATA[J SC (mA / cm 2 )]]> PCE(%) Front Sweep 1.80 84.0 20.0 30.2 Backsweep 1.80 85.4 20.0 30.7
[0058] Example 5
[0059] The present embodiment provides a crystalline silicon-perovskite tandem solar cell, comprising a crystalline silicon bottom cell and a perovskite top cell, wherein the crystalline silicon in the crystalline silicon bottom cell has a composite optical structure consisting of a micron-optical structure and a nano-optical structure, the micron-optical structure is formed in situ on the surface of the crystalline silicon, the nano-optical structure is formed in situ on the micron-optical structure, the micron-optical structure is used to reduce the reflection loss at the interface between the perovskite and the air, the nano-optical structure serves as a nano-support for the nucleation and growth of perovskite grains and is used to reduce the reflection loss at the interface between the perovskite and the crystalline silicon; the micron-optical structure has a micron-column structure distributed in a periodic array, and the nano-optical structure has a nano-hole structure distributed in a periodic array.
[0060] It is prepared by the following steps: (1) The n-type polished crystalline silicon substrate was cleaned according to the RCA standard and the oxide layer was removed by HF. A micron mask was first prepared on the surface of the crystalline silicon using reactive ion etching technology. Then, single-sided micron etching was performed using a mixture of Cl2 and SF6 as the reaction gas under a chamber pressure of 25 Pa to obtain a micron optical structure with a periodic array distribution. (2) using a counter-ion etching technique to perform nano-etching on the micron optical structure in step (1), first preparing a nano-mask on the surface of crystalline silicon, and then using a mixture of Cl2, SF6 and O2 as a reaction gas and a chamber pressure of 15 Pa to perform nano-etching to prepare a nano-optical structure with a periodic array distribution, thereby obtaining a composite optical structure crystalline silicon; (3) The two sides of the composite optical structure crystalline silicon were treated with concentrated nitric acid to generate a silicon oxide passivation layer. Then, the PECVD deposition technology was used to deposit phosphorus- and boron-doped amorphous silicon thin film precursors on the silicon oxide layers on both sides of the composite optical structure crystalline silicon. The thin film was annealed at 850 °C for 60 min in a tube furnace to crystallize the thin film and activate the doped atoms to form n- and p-type polycrystalline silicon transport layers, thereby obtaining a crystalline silicon bottom cell. (4) First, remove the oxide layer of the crystalline silicon bottom cell in step (3) by HF, deposit aluminum oxide on the front and back surfaces of the crystalline silicon bottom cell by an atomic layer deposition system, and then anneal and inject hydrogen; deposit a buffer layer by thermal evaporation; then deposit a TCO composite layer by PVD deposition technology; deposit a MeO-2PACz hole transport layer on the side of the crystalline silicon bottom cell with an n-type polycrystalline silicon transport layer by spin coating technology; deposit a perovskite film on the surface of the MeO-2PACz hole transport layer by spin coating technology; deposit C60 and bathocuproine (BCP) electron transport layers on the surface of the perovskite film by thermal evaporation; deposit an IZO transparent electrode on the BCP surface by magnetron sputtering deposition technology; and deposit a metal frame electrode on the surface and back of the IZO by magnetron sputtering deposition technology to obtain a crystalline silicon-perovskite stacked solar cell.
[0061] Example 6
[0062] The present embodiment provides a crystalline silicon-perovskite tandem solar cell, comprising a crystalline silicon bottom cell and a perovskite top cell, wherein the crystalline silicon in the crystalline silicon bottom cell has a composite optical structure consisting of a micron-optical structure and a nano-optical structure, the micron-optical structure is formed in situ on the surface of the crystalline silicon, the nano-optical structure is formed in situ on the micron-optical structure, the micron-optical structure is used to reduce the reflection loss at the interface between the perovskite and the air, the nano-optical structure serves as a nano-support for the nucleation and growth of perovskite grains and is used to reduce the reflection loss at the interface between the perovskite and the crystalline silicon; the micron-optical structure has a micron-tube structure distributed in a periodic array, and the nano-optical structure has a nano-tube structure distributed in a periodic array.
[0063] It is prepared by the following steps: (1) The n-type polished crystalline silicon substrate is cleaned according to the RCA standard and the oxide layer is removed by HF. A nanoimprint etching technique is used to first prepare a micron tube pattern template for nanoimprint etching, and the micron tube pattern template is imprinted on the surface of the crystalline silicon by nanoimprinting. Then, plasma etching is performed to obtain a micron optical structure with a periodic array distribution. (2) using nanoimprint etching technology to nano-etch the micron optical structure in step (1), first preparing a nanotube pattern template for nanoimprint etching, imprinting the nanotube pattern template on the surface of crystalline silicon by nanoimprinting, and then etching with plasma to prepare a nano-optical structure with a nanotube structure, thereby obtaining a composite optical structure crystalline silicon; (3) Treat both sides of crystalline silicon with concentrated nitric acid to generate a silicon oxide passivation layer. Then, use PECVD deposition technology to deposit phosphorus- and boron-doped amorphous silicon thin film precursors on the silicon oxide layers on both sides of the crystalline silicon. Anneal in a tube furnace at 1000 °C for 20 min to crystallize the thin film and activate the doped atoms to form n- and p-type polysilicon transport layers, thereby obtaining a crystalline silicon bottom cell. (4) First, remove the oxide layer of the crystalline silicon bottom cell in step (3) by HF, deposit aluminum oxide on the front and back surfaces of the crystalline silicon bottom cell by an atomic layer deposition system, and then anneal and inject hydrogen; deposit a buffer layer by thermal evaporation; then deposit a TCO composite layer by PVD deposition technology; deposit a MeO-2PACz hole transport layer on the side of the crystalline silicon bottom cell with an n-type polycrystalline silicon transport layer by spin coating technology; deposit a perovskite film on the surface of the MeO-2PACz hole transport layer by spin coating technology; deposit C60 and bathocuproine (BCP) electron transport layers on the surface of the perovskite film by thermal evaporation; deposit an IZO transparent electrode on the BCP surface by magnetron sputtering deposition technology; and deposit a metal frame electrode on the surface and back of the IZO by magnetron sputtering deposition technology to obtain a crystalline silicon-perovskite stacked solar cell.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A crystalline silicon-perovskite tandem solar cell, characterized in that: It comprises a crystalline silicon bottom cell and a perovskite top cell, wherein the crystalline silicon in the crystalline silicon bottom cell has a composite optical structure, wherein the composite optical structure comprises a micron optical structure and a nano-optical structure, wherein the micron optical structure is formed in situ on the surface of the crystalline silicon, wherein the nano-optical structure is formed in situ on the micron optical structure, wherein the micron optical structure has a micron structure distributed in a periodic array or randomly, and wherein the nano-optical structure has a nanostructure distributed in a periodic array or randomly.
2. The crystalline silicon-perovskite tandem solar cell according to claim 1, characterized in that: The crystalline silicon bottom cell is a silicon homojunction and a silicon heterojunction; And / or, the perovskite top cell is a perovskite solar cell based on a pin or nip structure; and / or, the microstructures include one or more of microholes, microcolumns, microcones, microtubes, microspheres, microhemispheres, micropyramids, microinverted pyramids and microbars; and / or, the nanostructure comprises one or more of a nanohole, a nanowire, a nanocolumn, a nanocone, a nanotube, a nanosphere, a nanohemisphere, a nanopyramid, a nanoinverted pyramid and a nanostrip; and / or, the size of the microstructure is 1-50 μm; And / or, the size of the nanostructure is 0.1-500 nm.
3. The crystalline silicon-perovskite tandem solar cell according to claim 2, characterized in that: The crystalline silicon bottom cell has any one of the cell structures of a tunneling oxygen passivation contact silicon bottom cell, a heterojunction silicon bottom cell, a full back electrode contact silicon bottom cell and a passivation emitter back field contact silicon bottom cell; and / or, the size of the microstructure is 5-20 μm; And / or, the size of the nanostructure is 10-300 nm.
4. A method for preparing a crystalline silicon-perovskite tandem solar cell according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. performing micron etching on the surface of a crystalline silicon substrate to form a micron optical structure with a periodic array distribution or a random distribution; S2, performing nano-etching on the surface of the micron optical structure in step S1 to form a nano-optical structure with a periodic array distribution or a random distribution, and obtaining a composite optical structure crystalline silicon; S3, depositing a passivation layer on both sides of the composite optical structure crystalline silicon in step S2, and then depositing an n-type transmission layer or a p-type transmission layer on the passivation layers on both sides of the composite optical structure crystalline silicon, respectively, and then depositing an intermediate composite layer on the front side of the composite optical structure crystalline silicon to obtain a crystalline silicon bottom cell preform; S4. On the front side of the crystalline silicon bottom cell preform described in step S3, a perovskite transmission layer, a perovskite active layer, a perovskite transmission layer, a front electrode buffer layer, a front electrode, a back electrode and a front anti-reflection layer are sequentially deposited to obtain a crystalline silicon-perovskite laminated solar cell.
5. The method for preparing a crystalline silicon-perovskite tandem solar cell according to claim 4, characterized in that: The micro-etching and the nano-etching adopt wet etching and / or dry etching, the wet etching includes one or more of immersion etching, spray etching and photolithography, and the dry etching includes one or more of physical etching, chemical etching and physicochemical etching.
6. The method for preparing a crystalline silicon-perovskite tandem solar cell according to claim 5, characterized in that: The wet etching is solution etching; And / or, the dry etching is reactive ion etching or nanoimprint etching; And / or, the deposition method of the perovskite transport layer is solution deposition.
7. The method for preparing a crystalline silicon-perovskite tandem solar cell according to claim 6, characterized in that: The solution composition of the solution etching comprises one or more of potassium hydroxide, sodium hydroxide and tetramethylammonium hydroxide; And / or, the process of reactive ion etching is to prepare a micron / nanometer mask layer on the surface of the crystalline silicon and then perform reactive ion etching; And / or, the solution deposition comprises any one of spin coating, blade coating and slit coating.
8. The method for preparing a crystalline silicon-perovskite tandem solar cell according to claim 7, characterized in that: The solution composition also includes additives; And / or, the reactive gas for reactive ion etching is any one of a mixed gas of Cl2 and SF6, Cl2, SF6 and O2, Cl2, SF6, CF4 and O2, or Cl2, BCl3 and Ar; And / or, the chamber pressure of the reactive ion etching is 15-25 Pa.
9. The method for preparing a crystalline silicon-perovskite tandem solar cell according to claim 8, characterized in that: The additive includes isopropyl alcohol; And / or, the process of the nanoimprint etching is to prepare a pattern template for nanoimprint etching, imprint the pattern template on the surface of the crystalline silicon by nanoimprinting, and then perform etching.
10. The method for preparing a crystalline silicon-perovskite tandem solar cell according to claim 5, characterized in that: The nano-etching method also includes a pore expansion process, wherein the pore expansion process is as follows: firstly placing the nano-optical structure in a solution containing acid, alkali or hydrogen peroxide for pore expansion, then removing the surface oxide layer with hydrofluoric acid, and then removing the surface metal ions with nitric acid.
Citation Information
Patent Citations
Perovskite solar cell based on silicon-based micro-nano structure and production method of perovskite solar cell
CN106159094A
Silicon perovskite laminated solar cell with nano-scale liquid film creeping resistance-increasing layer and preparation method thereof
CN109545973A